Založení objektu v Karlových Varech - Hrdý, Roman (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Tato diplomová práce se zabývá založením polyfunkčního domu v Karlových Varech. Cílem je navrhnout bezpečné, hospodárné a funkční řešení pro pažení podzemních pater budovy a návrh základových konstrukcí.

This thesis deals with the foundation of multifunctional building in Karlovy Vary. The aim of this thesis is to design a safe, economical and functional solutions for sheeting underground floors of the building and design of foundation structures.
The Design of Foundation of Building in Karlovy Vary
Keywords: Stavební jáma; piloty; kotva; zakládání staveb; pažení; geotechnický průzkum; zatížení; vrtané piloty; Foundation pit; piles; anchor; building foundation; sheeting; geotechnical survey; load; bored piles